1989
DOI: 10.1099/00207713-39-2-185
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Ribonucleic Acid Cistron Similarities and Deoxyribonucleic Acid Homologies of Neisseria, Kingella, Eikenella, Simonsiella, Alysiella, and Centers for Disease Control Groups EF-4 and M-5 in the Emended Family Neisseriaceae

Abstract: Federal Republic of Germany2 We detected distinct taxonomic relationships among the true Neisseria species, Kingella kingae, Kingella denitrGcans, Eikenella corrodens, all Simonsiella species, the type strain of Alysiellafiliformis, and members of Centers for Disease Control groups EF-4 and M-5. All these taxa constitute one large separate cluster having high levels of ribosomal ribonucleic acid cistron similarity (thermal denaturation temperature range, 74 to 81°C) in ribosomal ribonucleic acid superfamily 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
45
2
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 35 publications
7
45
2
1
Order By: Relevance
“…Phylogenetically, the family encompasses the genera Neisseria, Kingella, Eikenella, Simonsiella and Alysiella (Dewhirst et al, 1989;Rossau et al, 1989). It is clear from the results of the present study that the unidentified bacterium from pigs is phylogenetically a member of this family grouping.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…Phylogenetically, the family encompasses the genera Neisseria, Kingella, Eikenella, Simonsiella and Alysiella (Dewhirst et al, 1989;Rossau et al, 1989). It is clear from the results of the present study that the unidentified bacterium from pigs is phylogenetically a member of this family grouping.…”
supporting
confidence: 54%
“…On the basis of rRNA cistron similarity studies, Rossau et al (1986) recommended that the genera Acinetobacter, Moraxella and Branhamella be excluded from the family Neisseriaceae. Subsequent studies by Rossau et al (1989) showed that the genera Neisseria, Kingella, Eikenella, Simonsiella and Alysiella were closely related and should be classified together in the family Neisseriaceae, which comprises a major branch of the b-Proteobacteria. Comparative 16S rRNA gene sequencing studies by Dewhirst et al (1989) confirmed the results of Rossau et al (1989) and led to the recommendation that the genera Eikenella and Simonsiella be transferred to the family Neisseriaceae.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This problem is being encountered with increasing frequency as ribosomal cistron analysis and 16s rRNA sequencing studies show that organisms with major phenotypic differences are closely related genomically. For example, the facultatively anaerobic organism Eikenella corrodens is clearly a member of the aerobic family Neisseriaceae (10,28). In addressing this problem, we were guided by the advice presented by Wayne et al (44).…”
Section: U~c a C U G C A U G A A W C G G A A U C G C U A W A A U C G mentioning
confidence: 99%
“…Kingella indologenes has been recovered from human eye infections and from the blood of a patient with endocarditis (15,39,42). It has been reported previously that Kingella indologenes is not closely related to other Kingella species (10,28) and thus is generically misnamed. Bacteroides nodosus is the essential causative agent of footrot in sheep, * Corresponding author.…”
mentioning
confidence: 99%